A forecasting method in data envelopment analysis with group decision making. (22nd January 2010) - Kiani Mavi, Reza; Makui, Ahmad; Fazli, Safar; Alinezhad, Alireza
Service companies continually seek improved methods to measure the performance of their organisations because they are committed to improve efficiency and effectiveness in their operating units. Managers generally regard conventional methods inadequate. They struggle with the existing methodology as they are trying to implement the results obtained from such processes as performance ratios, regression analysis results and the like. DEA has proven itself to be both theoretically sound framework for performance measurement and an acceptable method by those being measured. In this paper, by combining group analytic hierarchy process (GAHP) into data envelopment analysis (DEA), a new approach for forecasting is developed. The efficiency of this approach is tested with application in bank branches. According to the results, this approach has more advantages over conventional methodologies.